Corticotroph tumor progression after bilateral adrenalectomy: data from ERCUSYN. Issue 12 (2nd November 2022) - Valassi, Elena; Castinetti, Frédéric; Ferriere, Amandine; Tsagarakis, Stylianos; Feelders, Richard A; Netea-Maier, Romana T; Droste, Michael; Strasburger, Christian J; Maiter, Dominique; Kastelan, Darko; Chanson, Philippe; Webb, Susan M; et al.
Abstract : Corticotroph tumor progression after bilateral adrenalectomy/Nelson's syndrome (CTP-BADX/NS) is a severe complication of bilateral adrenalectomy (BADX). The aim of our study was to investigate the prevalence, presentation and outcome of CTP-BADX/NS in patients with Cushing's disease (CD) included in the European Registry on Cushing's Syndrome (ERCUSYN). We examined data on 1045 CD patients and identified 85 (8%) who underwent BADX. Of these, 73 (86%) had follow-up data available. The median duration of follow-up since BADX to the last visit/death was 7 years (IQR 2–9 years). Thirty-three patients (45%) experienced CTP-BADX/NS after 3 years (1.5–6) since BADX. Cumulative progression-free survival was 73% at 3 years, 66% at 5 years and 46% at 10 years. CTP-BADX/NS patients more frequently had a visible tumor at diagnosis of CD than patients without CTP-BADX/NS ( P  < 0.05). Twenty-seven CTP-BADX/NS patients underwent surgery, 48% radiotherapy and 27% received medical therapy. The median time since diagnosis of CTP-BADX/NS to the last follow-up visit was 2 years (IQR, 1–5). Control of tumor progression was not achieved in 16 of 33 (48%) patients, of whom 8 (50%) died after a mean of 4 years. Maximum adenoma size at diagnosis of CD was associated with further tumor growth in CTP-BADX/NS despite treatment ( P  = 0.033). Diagnosis of CTP-BADX/NS, older age, greater UFC levels at diagnosis of CD and initial treatment predicted mortality. In conclusion, CTP-BADX/NS was reported in 45% of the ERCUSYN patients who underwent BADX, and control of tumor growth was reached in half of them. Future studies are needed to establish effective strategies for prevention and treatment.